S-Process in massive carbon-enhanced metal-poor stars. Issue 4 (17th August 2018) - Banerjee, Projjwal; Qian, Yong-Zhong; Heger, Alexander
ABSTRACT: Observations suggest that the interstellar medium (ISM) might have been highly enriched in carbon at very early times. We explore nucleosynthesis in massive carbon-enhanced metal-poor (CEMP) stars of 12–$40\, M_\odot$ formed from such an ISM with [Fe] ≤ −2. We find substantial production of elements heavier than Fe, mostly up to Sr, by the weak s-process in stars with initial abundances of [CNO] ≳ −1.5. Even heavier elements, up to Ba, can be produced for [CNO] ≳ −0.5. The efficiency of this s-process is sensitive to the initial enhancement of C (or more generally, CNO) and mass of the star, with the yield increasing approximately linearly with the initial Fe abundance. The s-process in CEMP stars of ${\gtrsim } 20 \, M_\odot$ with [CNO] ≳ −1.5 can be an important source for heavy elements in the early Galaxy.